(untitled) (Boston, 2010)
The legal and Regulatory enviroment of Business combines a classic "black letter law" approach with an interesting and accessible reader-friendly format. The cases, content, and features of the exciting new Eighth Edition have been thoroughly updated to represent the latest developments in the business law environment.
Keywords: Trade regulation,Commercial law,Industrial laws and legislation,Quy định thương mại,Luật thương mại,Luật Công nghiệp và văn bản luật; United States,United States,United States,Mỹ,Mỹ,Mỹ